Tax evasion and cognitive dissonance - Klaus Beckmann; Susan Gattke (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
We introduce public signals and cognitive dissonance into the standard Allingham-Sandmo-Yitzhaki (ASY) model of tax evasion. It turns out that the presence of cognitive dissonanceattenuates tax evasion as individuals dislike allowing their true bevhaviour to diverge from their public statement of the 'admissible' degree of tax evasion, which, in turn, they use to influence the probability of detection. Some potential policy conclusions and extensions are discussed.
Keywords: H26; H30; D03; 330; tax evasion; cognitive dissonance; public signals